Mourning Salazar: the ideologic oriented grief in the Portuguese newspapers during the dictatorship - Mota,Joana Martins (2020)
Abstract Death is one of the most prominent news values, especially when combined with another characteristic of newsworthiness: the notoriety of the individual. Based on the combination of death and prominence of the personality, this paper proposes an approach to media discourses on the death of the political Portuguese leader, António de Oliveira Salazar, former President of the Council during the dictatorial regime, known as Estado Novo (New State). Considering the newspapers published at the time of his death, July, 1970, and taking into account the existence of the censorship, this study analyzes the coverage of the event, as well as the apologetical discourse used by the journalists and the newsworthiness of the event.